PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN MODEL PEMBELAJARAN MAKE A MATCH PADA SISWA SEKOLAH DASAR - Nur Hidayah; Sagita Nur ‘Aeni, Erlina Dwi Cahyani, Syifa Nur Hidayah, Devi Mukti Safila, Sairotul Fadhilah, Puji (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to determine the improvement of ips learning outcomes using the make a match learning model in elementary school students. This research is a qualitative research which is a descriptive research. The research method used in this research is the library research method. The data from this research was analyzed descriptively. The results of this study indicate that there is an increase in ips learning outcomes using the make a match learning model in elementary school students.